TECHNOLOGY CONTINUANCE THEORY DALAM ONLINE CUSTOMER EXPERIENCE UNTUK MENINGKATKAN KONTINUITAS PENGGUNAAN M-WALLET PADA GENERASI Z - Wibowo, Gilang Rahmat; Masnita, Yolanda; Kurniawati (FEB Universitas Sam Ratulangi Manado, 2025)
Post-use research on m-Wallet needs to be considered to retain its users. The gamification effect assisted by Online Customer Experience is an option to increase user trust in using m-Wallet to increase continued usage intentions. In this study, data collection was conducted by distributing questionnaires online to generation Z and collected 297 respondents. This study shows that attitude, gamification and usefulness have a positive effect on m-Wallet continous intention. The moderating effect on Online Customer Experience was also found to have a positive effect on m-Wallet continous intention. Further research is expected to further explore other characteristics such as other generations, age, education, and occupation.